2021
DOI: 10.30734/jpe.v8i2.1334
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students' Critical Thinking during Covid-19 through Online Learning

Abstract: The application of Problem Based Learning model by online learning during the Covid-19 period is one way to improve students' thinking abilities. This research aims to obtain empirical data about the comparison of student's critical thinking skills levels by using the online based Problem Based Learning (PBL) model using the Zoom application and Whatsapp Grup in class X IPS SMAN 5 Tangerang Regency. The method of this research used quantitative that is quasi-experimental design. This research's samples were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, Ghazizadeh and Fatemipour (2017), Oweis (2018), Hijazi and AlNatour (2020), Sharma and Sharma (2020) confirmed the current results. Recent studies from 2022, such as Apsari and Parmawati (2022), Fardin et al (2022), Mohamed (2022), andMiraei Mohammadi et al (2022), all validated the findings where statistically significant differences existed favouring blended learning over traditional face-to-face learning. The study findings were different from the other studies in that gender do not interact differently toward blended learning strategies.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, Ghazizadeh and Fatemipour (2017), Oweis (2018), Hijazi and AlNatour (2020), Sharma and Sharma (2020) confirmed the current results. Recent studies from 2022, such as Apsari and Parmawati (2022), Fardin et al (2022), Mohamed (2022), andMiraei Mohammadi et al (2022), all validated the findings where statistically significant differences existed favouring blended learning over traditional face-to-face learning. The study findings were different from the other studies in that gender do not interact differently toward blended learning strategies.…”
mentioning
confidence: 75%
“…The use of blended learning to improve EFL reading comprehension achievement would be extremely beneficial to Libyan students (Belazi & Ganpathy, 2021). Face-to-face teaching is one of the most critical instruments for obtaining foreign language input, and using blended learning to improve EFL achievement would be extremely beneficial to Libyan students (Apsari & Parmawati, 2022). unluckily, old methods of teaching English to EFL students are still in use in the Libyan educational system, and many Libyan teachers are ignorant of this relatively recent trend in language teaching (Belazi & Ganapathy, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to statistical analysis, the posttest score is higher than the score of the pretest test findings. Several researchers, including (Aufa, Rusmansyah, Hasbie, Jaidie, & Yunita, 2021; Kamid, Anggereini, & Muhtadin, 2018;Putri & Hasbi, 2018;Sabur, Saepuloh, & Triana, 2021;Suwarno, Wahidin, & Nur, 2020;Wondo, Meke, & Sao, 2021) have found that using problem-based learning models in learning may increase investigation, analysis, assessment, and drawing conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Peserta didik berpartisipasi aktif dalam kegiatan pembelajaran bahkan ketika diskusi kelas dimulai dan setiap kelompok bersaing untuk menjadi kelompok yang aktif dengan berpartisipasi dalam proses tanya jawab yang diberikan guru. Peserta didik dapat membiasakan menghadapi tantangan dan memecahkan masalah dengan menganalisis pemikirannya sendiri untuk membuat keputusan dan menarik kesimpulan tentang keputusan atau tindakan yang diambil (Lestari et al, 2023;Sabur et al, 2021;Yulianti et al, 2020).…”
Section: Temuan Keduaunclassified